(untitled) (Global Journal of Human-Social Science, 2023)
Hasten slowly are two simple antonymous words consisting of a simple self- contradictory statement ladening with the grave meaning of life It seems to be surprising glancing that two inter-penetrated words are juxtaposed together to erupt the curiosity of the readers about its use and function The very word Hasten emerges from the word haste denoting the meaning of the word quick and hasten is the verbal derivative of the word haste laybaring the exegesis of quicken What is about slowly It epitomizes the reverse meaning of quickly So what does the statement mean Actually it connotes the sense of doing anything quickly meticulously and sincerely It is the trek of hurriedness with sincerity and dedication This hasten slowly goes quite opposite to the sense and sensibility of the two heinous bents of mind of modern era zero error syndrome and no reaction time These two unnecessary evil tendencies pave the way to the suffocation of modern people de-capacitating their work spirit and abating the work standard Thus hasten slowly should be positively nurtured to eliminate these two phrasal expressions of morbid mindset